Subtitling At the Crossroads: the Subtitle’s Context Challenging the Subtitling Practice? - Chelli , Madjda (Journal of Human Sciences, 2023)
The surge of new audiovisual genres such as reality shows has led to new challenges to subtitlers. New questions such as spotting and the translation of written information on the screen have emerged. This paper aims at highlighting the challenges posed by the complex nature of the subtitle’s context to the subtitling practice. It sets to answer the following question: what is the effect of the subtitling strategies of culture bound terms on the quality of subtitle synchronization? It goes through qualitative analysis of authentic examples of subtitles from The Moment of Truth and cooking programmes on MBC4 and Fatafeat respectively, based on Pederson’s typology (2011). The results showed a high-level of discrepancy between oral and written texts that could be easily detected by the viewers. Significantly, the complex nature of the subtitle’s context is an emerging constraint on the subtitling practice.